7 - Analyse géographique du parcours sciences et techniques. Cas de L’université de NGaoundéré - Mediebou Chindji,; Michel Tchotsoua, (Journal of Higher Education in Africa, 2012)
The author of this paper evaluates the contribution of qualified scientists and trained engineers in science and technology of the University of Ngaoundere to the development of Northern-Cameroon. In order, a questionnaire survey was conducted among its graduate students who have a job. The technique of a snowball contact made it possible to survey 360 graduates Yaounde, Douala and in the main cities of Northern-Cameroon. The analysis of all this data was done using descriptive statistics methods. The results show that the University of Ngaoundere has contributed not only to the training of human resources in this region, but has also resulted in a change in the economic organization and a diversification of the job market even if these impacts are low on sectors capable of generating development.